2023
DOI: 10.1111/adj.12951
|View full text |Cite
|
Sign up to set email alerts
|

Orifice barriers to prevent coronal microleakage after root canal treatment: systematic review and meta‐analysis

Abstract: Aims: This systematic review aimed to compare the efficiency of orifice barriers in preventing coronal microleakage in vitro. Methods: Articles published in English, German and Chinese were searched for studies describing microleakage assays for the bacterial penetration of root canal-treated teeth in vitro. The final sample included 18 articles for review and meta-analysis. Risk ratios and confidence intervals were determined for dichotomous variables. Ten publications using bacterial leakage models contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Orifice barriers, sometimes referred to as "intra-orifice barriers," "coronal plugs," or "orifice plugs," are restorative materials that are placed into root canal orifices (at or just below canal orifice level) and used as a base to cover the pulp chamber floor once the root canal treatment is completed [55]. Different materials can be used such as Glass ionomer cement, Resin modified GIC, Composite resin, Mineral trioxide aggregate, and Cavit [56]. A recent systematic review and metaanalysis study in which orifice barriers were used to prevent coronal microleakage after root canal obturation concluded that orifice barriers are effective in preventing coronal microleakage and should be placed after the completion of root canal treatment [56].…”
Section: Coronal Seal Of Root Canal Treated Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…Orifice barriers, sometimes referred to as "intra-orifice barriers," "coronal plugs," or "orifice plugs," are restorative materials that are placed into root canal orifices (at or just below canal orifice level) and used as a base to cover the pulp chamber floor once the root canal treatment is completed [55]. Different materials can be used such as Glass ionomer cement, Resin modified GIC, Composite resin, Mineral trioxide aggregate, and Cavit [56]. A recent systematic review and metaanalysis study in which orifice barriers were used to prevent coronal microleakage after root canal obturation concluded that orifice barriers are effective in preventing coronal microleakage and should be placed after the completion of root canal treatment [56].…”
Section: Coronal Seal Of Root Canal Treated Teethmentioning
confidence: 99%
“…Different materials can be used such as Glass ionomer cement, Resin modified GIC, Composite resin, Mineral trioxide aggregate, and Cavit [56]. A recent systematic review and metaanalysis study in which orifice barriers were used to prevent coronal microleakage after root canal obturation concluded that orifice barriers are effective in preventing coronal microleakage and should be placed after the completion of root canal treatment [56].…”
Section: Coronal Seal Of Root Canal Treated Teethmentioning
confidence: 99%
“…[72][73][74][75][76][77][78][79][80] A recent systematic review and meta-analysis concluded that various materials placed as OBs are effective in the prevention of microleakage in vitro. 81 However, insufficient data prevented statistical comparisons from being made. In fact, the heterogeneity and weak design of this type of study have led several prominent journals to refuse publication of studies based on assessment of microleakage 82,83 due to inconsistency of study design and the lack of clinical relevance.…”
Section: Orifice Barriersmentioning
confidence: 99%
“…Many studies have investigated the efficacy of OBs, testing a variety of materials including amalgam, conventional glass‐ionomer cements, resin‐modified glass‐ionomer cements, resin composites, zinc polycarboxylate cements (ZPC), mineral trioxide aggregate (MTA) and calcium silicate‐based cements (CSC) 72–80 . A recent systematic review and meta‐analysis concluded that various materials placed as OBs are effective in the prevention of microleakage in vitro 81 . However, insufficient data prevented statistical comparisons from being made.…”
Section: Orifice Barriersmentioning
confidence: 99%
“…Recent laboratory research indicates that within a few days of exposure to saliva, substantial leakage occurs at the coronal portion of the root canal filling, ranging from 33% to 85% of the total length of the root [ 5 , 6 ]. Insufficient temporary restorations during endodontic treatment rank as the second most significant factor contributing to ongoing pain after treatment initiation, following inadequate debridement or incomplete removal of the pulp tissue, which stands as the primary cause [ 7 ].…”
Section: Introductionmentioning
confidence: 99%